Theories of learning for the workplace : building blocks for training and professional development programmes - Dochy, Filip [Verfasser]; Gijbels, David [Verfasser]; Segers, Mien [Verfasser]; Van den Bossche, Piet [Verfasser] (Routledge, 2011)
"Workplace and professional learning, lifelong learning, adult learning and learning in different contexts have become of more and more interest and now dominate all aspects of twenty-first-century life. Learning is no longer about 'storing and recall' but 'development and flow'. Theories of Learning for the Workplace offers fascinating overviews into some of the most important theories of learning and how they are practically applied to organisational or workplace learning. With each chapter co-authored by an academic researcher and an expert in business or industry, this unique book provides practical case studies combined with thorough analyses of theories and models of learning. Key figures in education, psychology and cognitive science present a comprehensive range of conceptual perspectives on learning theory, offering a wealth of new insights to support innovative research directions." (Publisher, BIBB-Doku)
Keywords: T 2.2 Lerntheorien; L 2.1.3 Erfahrungslernen; Lerntheorie; Erwachsenenbildung; Lernen am Arbeitsplatz; Informelles Lernen; Erfahrungsorientiertes Lernen; Lernende Organisation